CO2-concentration of the surrounding air of sleeping infants inside a crib. Issue 3 (8th December 2021) - Braun, Gert-Jan; Zeiler, Wim
Abstract: The indoor air quality is important for the well-being of humans, especially in the case of young babies. This research focuses on the air qualityinside a crib with sleeping infants. The effects of different sleeping positions of the baby on the air quality within the crib were studied by measurements on modelled setup. The breathing of an infant was simulated by means of a baby doll which had a breathing device: a intermitted supply of air mixed with CO2 through a tube in the lips of the baby doll. For different sleeping positions, the effects on the CO2 concentration inside the baby bed were measured and compared with the background CO2 -level in the sleeping quarter. The results showed an increased CO2 concentration (up to 4 times) depending on the sleeping position of the infant.